Three positive feedback mechanisms for ice-sheet melting in a warming climate - Ren, Diandong; Leslie, L. (International Glaciological Society, 2011)
Three positive feedback mechanisms that accelerate ice-sheet melting are assessed in a warming climate, using a numerical ice model driven by atmospheric climate models. The Greenland ice sheet (GrIS) is the modeling test-bed under accelerated melting conditions. The first feedback is the interaction of sea water with ice. It is positive because fresh water melts ice faster than salty water, owing primarily to the reduction in water heat capacity by solutes. It is shown to be limited for the GrIS, which has only a small ocean interface, and the grounding line of some fast glaciers becomes land-terminating during the 21st century. The second positive feedback, strain heating, is positive because it produces further ice heating inside the ice sheet. The third positive feedback, granular basal sliding, applies to all ice sheets and becomes the dominant feedback during the 21st century. A numerical simulation of Jakobshavn Isbrae over the 21st century reveals that all three feedback processes are active for this glacier. Compared with the year 2000 level, annual ice discharge into the ocean could increase by ~1.4 km3 a–1 (~5% of the present annual rate) by 2100. Granular basal sliding contributes ~40% of this increase.